2015
DOI: 10.1002/2015gl064816
|View full text |Cite
|
Sign up to set email alerts
|

Pileup accident hypothesis of magnetic storm on 17 March 2015

Abstract: We propose a “pileup accident” hypothesis, based on the solar wind data analysis and magnetohydrodynamics modeling, to explain unexpectedly geoeffective solar wind structure which caused the largest magnetic storm so far during the solar cycle 24 on 17 March 2015: First, a fast coronal mass ejection with strong southward magnetic fields both in the sheath and in the ejecta was followed by a high‐speed stream from a nearby coronal hole. This combination resulted in less adiabatic expansion than usual to keep th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 26 publications
2
101
1
Order By: Relevance
“…In particular at increasing heliospheric distances ICMEs get more and more engulfed into fast streams and they become part of larger-scale heliospheric structures called compound streams (e.g., Burlaga et al 1987). On the other hand, an ICME may also collide with a slower and higher density heliospheric plasma sheet ahead, which may compress its front part (see e.g., Kataoka et al 2015).…”
Section: Observations Of Icme Interactions In the Heliospherementioning
confidence: 99%
“…In particular at increasing heliospheric distances ICMEs get more and more engulfed into fast streams and they become part of larger-scale heliospheric structures called compound streams (e.g., Burlaga et al 1987). On the other hand, an ICME may also collide with a slower and higher density heliospheric plasma sheet ahead, which may compress its front part (see e.g., Kataoka et al 2015).…”
Section: Observations Of Icme Interactions In the Heliospherementioning
confidence: 99%
“…The most intense geomagnetic storm in the rising-maximum phases of cycle 24 is the 17 March 2015 storm, currently called as 'the St. Patrick's Day storm' , with the minimum Dst index of −223 nT (Kamide and Kusano 2015). Kataoka et al (2015) noted that this storm was intensified by interaction of a CME and following high-speed stream shortly before its arrival at the Earth. According to Table 1, occurrence of the geomagnetic storms in cycle 24 showed two-peak characteristics.…”
Section: Geomagnetic Storms In the Rising-maximum Phases Of Cycle 24mentioning
confidence: 99%
“…In the mesosphere, strong echoes were detected at heights of 60 to 80 km over this time period. These polar mesosphere winter echoes (PMWEs) are likely initiated by increased ionization during the solar flare event occurring on 17-18 March 2015 (Kataoka et al, 2015;Jacobsen and Andalsvik, 2016;Cherniak and Zakharenkova, 2016). In this period, the polar night jet was in the phase of formation around Syowa Station at the stratopause (at the height of about 55 km; not shown).…”
Section: Initial Condition and Other Physical Schemesmentioning
confidence: 99%
“…See Sato et al (2014) for further information on the PANSY radar system and for a list of future studies to be conducted based on this system. For the 16-24 March 2015 period, strong polar mesosphere winter echoes, which likely resulted from the largest magnetic storm event occurring during the solar cycle 24 ("St. Patrick's Day storm"; Kataoka et al, 2015;Jacobsen and Andalsvik, 2016;Cherniak and Zakharenkova, 2016), were observed by the PANSY radar system.…”
Section: The Pansy Radar Observationsmentioning
confidence: 99%